Earth's water cycle - Bauman, Amy. (Pleasantville, NY : Gareth Stevens Pub., 2008)
Simple text, facts, photographs, diagrams, and related activities describe the water cycle and explain how it affects Earth.
The blue planet -- Water, water everywhere -- Water in action -- Saving water.
Includes index.
Library Media Connection.
5.5
5-8
Keywords: Hydrologic cycle -- Juvenile literature; Hydrologic cycle; Water; Water